The Tribulations of the Sargent Major. Conflicts of Jurisdiction and Cross Border Relationships in the South of Santiago del Estero at the end of the 18th Century (Quinto Sol, 2021)
Through the judicial adventures of Sergeant Major Gabriel Guillermo Espínola, a member of a paradigmatic family in the area, this article delves into social relationships and local political history in two dimensions. Accused of stealing livestock through his protégés and abusing his authority as a judge, the process against Espínola illuminates, on one hand, the kinship, obedience and dependency plots, as well as the conflicts of jurisdiction at the time of creation of the Tucumán “Intendencias” and expansion of the bailiffs in the countryside. On the other hand, it addresses Espínola's role as “Comandante de fronteras” near Concepción de Abipones and his close relationship with guaycurú Tribes in the Chaco region.
Keywords: frontier; colonial period; conflicts of jurisdiction